A Concept Design of Training Ship in Indonesia Waterway: Toward A Type of Passenger-Container Vessel - Rusi, Rusnaedi; Fitriah, Rifkah; Pettarani, Amrin; Rusi, Sudarman; AM, Andi Rachmianty; Baso, Suandar; Asis, Muhammad Akbar (Naval Architecture Departement, Hasanuddin University, 2022)
In the future, the seafaring profession will face some tough challenges. In order to address the challenges, the Maritime Vocational Education (MVE) is required to produce graduates with appropriate competencies related to the perspective of international trade in the shipping sector based on the Standards of Training, Certification and Watchkeeping for Seafarers (STCW). In order to improve the skills of students, a training ship is needed by maritime vocational education as a real practice for students. This study describes the concept of training ship design for maritime vocational education with consideration of Indonesian waters. The design concept starts with selecting the type of training ship, determining the capacity of the training ship, determining the main dimensions of the training ship design. Making line plans, making General Plan Drawings, calculating ship resistance taking into account Indonesian waters and determining the driving force of the main engine of the training ship as well as calculating the stability of the training ship. This design was applied to the AMI Makassar Maritime Polytechnic as a case study. The results showed that the type of Passenger-Container Vessel. The capacity of the training ship is around 150 students with a container load capacity of 8 TEUs. The main dimensions of the training ship design are the length between perpendicular (Lbp), width (B), height (H), and draft (T) respectively 69.23 m, 12.00 m, 5.50 m, and 2.54 m with Gross Tonage and ship engine power of 1.404,84 GT and 1090,7 Kwatts. The main dimensions of the training ship design are also corrected with the main dimension ratio parameters, geometric shape coefficients, weight and initial static stability.The seafaring profession will face some tough challenges today and in the future. Accordingly, Standards of Training, Certification and Watchkeeping for Seafarers (STCW)